Climatic-oceanic forcing on the organic accumulation across the shelf during the Early Cambrian (Age 2 through 3) in the mid-upper Yangtze Block, NE Guizhou, South China. (February 2017) - Yeasmin, Rumana; Chen, Daizhao; Fu, Yong; Wang, Jianguo; Guo, Zenghui; Guo, Chuan
Graphical abstract: Highlights: Integrated sedimentological and geochemical constraints on organic enrichment in the Early Cambrian, South China. Extraordinary high bioproductivity was fueled by wind-induced upwelling during transgressions under a relatively arid climate. Sulfidic water wedges only localized in the high-productivity zone on the shallow mid-upper slope of open shelf. Nonsulfidic anoxic waters extensive in the deeper open shelf basin or intrashelf basins landwards. Climatic-oceanic co-evolution controlled the high heterogeneities in productivity and redox states. Abstract: The organic-rich sediments were widely deposited over the entire Yangtze Block during the Early Cambrian (late Nemakit-Daldynian to Botomian). In the mid-upper Yangtze region, northeastern Guizhou, South China, they comprise, in ascending order, the Niutitang, Jiumenchong and lower Bianmachong formations which are dominated by black shales except the middle one characterized by interbedded shales-limestones. Three third-order depositional sequences are identified in the two studied sections located on the upper slope to basin of the open shelf. The organic-rich sediments were mostly deposited notably during transgressions on the shallower upper slope-margin (TOC up to 25 wt.%) where they are characterized by co-increases in C, P, Fe, and Ba concentrations, indicating the highest organic productivity and coupled C, P and Fe cycling there. In contrast, in the shelf basin, the concomitant organic-rich sediments yield lower organic (TOC <10 wt.% mostly) and Ba abundances, and generally show antithetic relationship of TOC with P and Fe variations, indicative of a relatively low organic productivity and transient decoupled C, P and Fe cycling in the deeper basin. This spatial difference in C, P, Fe and Ba cycling as a whole thus indicate that the highest organic productivity wedge on the shallower shelf upper slope-margin was likely induced by the oceanic upwelling from the restricted basin where the P and Fe nutrients were transiently depleted without timely renewal. Meanwhile, multiple redox proxies, including V/Al, Ni/Al and Cr/Al ratios vs. TOC contents, together with V/(V + Ni) and V/Cr ratios, generally characterize a more severe euxinic water wedge localized on the shallower upper slope-margin of shelf where the organic production culminated, but a nonsulfidic (ferruginous) anoxic state in the basin due to the relatively low sulfate level. Meanwhile, episodic depletion of trace elements in the deeper basin during the higher organic productivity also reconciles the concomitantly enhanced upwelling from the somewhat restricted deep watermass likely silled by the underwater upland seaward. The coincidence of organic-rich intervals with more arid climate epoches, as shown by increased Ti/Al ratios indicative of increased aeolian fluxes, reconciles a subtropical arid climate of Yangtze Block within the north mid-low-latitude trade-wind zone during deposition (the Early Cambrian). As such, enhanced offshore currents driven by the trade winds could have further induced the upwelling of nutrient-rich deep waters along the shelf during the transgressions, although tended to wane onwards, leading to the tempo-spatial heterogeneities in organic production and redox state across the shelf sea.